2008
DOI: 10.1021/ja803841n
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Formation of Off-Pathway Species during Folding of an α−β Parallel Protein Is Due to Docking of (Non)native Structure Elements in Unfolded Molecules

Abstract: Detailed information about unfolded states is required to understand how proteins fold. Knowledge about folding intermediates formed subsequently is essential to get a grip on pathological aggregation phenomena. During folding of apoflavodoxin, which adopts the widely prevalent alpha-beta parallel topology, most molecules fold via an off-pathway folding intermediate with helical properties. To better understand why this species is formed, guanidine hydrochloride-unfolded apoflavodoxin is characterized at the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
116
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(120 citation statements)
references
References 50 publications
4
116
0
Order By: Relevance
“…Figure S3), GED of dynamin in 9.7 M urea, 14 GED of dynamin in 6 M GuHCl, 15 SUMO from Drosophila melanogaster in 8 M urea, 16 and Azotobacter Vinelandii apoflavodoxin in 6 M GuHCl. 17 (Figure 2). To better account for sequence-dependent effects on chemical shifts, in principle, we could use amino acid triplets (or quintuples and so on); however, larger databases would be required to derive the corresponding parameters in these cases.…”
mentioning
confidence: 99%
“…Figure S3), GED of dynamin in 9.7 M urea, 14 GED of dynamin in 6 M GuHCl, 15 SUMO from Drosophila melanogaster in 8 M urea, 16 and Azotobacter Vinelandii apoflavodoxin in 6 M GuHCl. 17 (Figure 2). To better account for sequence-dependent effects on chemical shifts, in principle, we could use amino acid triplets (or quintuples and so on); however, larger databases would be required to derive the corresponding parameters in these cases.…”
mentioning
confidence: 99%
“…α-Crystallin distinguishes between MG states of α-lactalbumin, and preferentially interacts with MGs on route to aggregation and precipitation (66). GroEL, sometimes in combination with GroES, recognizes MGs and may stimulate their productive folding, though the exact mechanisms by which it does this are still not completely understood (67)(68)(69). In addition, the ribosome seems to have a protein folding activity through Domain V rRNA (70).…”
Section: Discussionmentioning
confidence: 99%
“…The folding of flavodoxin II from A. vinelandii (65,66) has been studied extensively. Un-and re-folding of both the apo-and the holo-form of this protein have been probed, using GuHCl as denaturant (67)(68)(69)(70)(71)(72)(73)(74). It has been shown that apoflavodoxin folds autonomously to its native state, after which it binds FMN as the last step in flavodoxin formation (Fig.…”
Section: Elucidating Cotranslational Folding Of Flavodoxinmentioning
confidence: 99%
See 2 more Smart Citations